The N17 domain of huntingtin as a multifaceted player in Huntington’s disease - Hyunju Cho (Frontiers in Molecular Biosciences)
Huntington’s disease (HD) is primarily caused by the aberrant aggregation of the N-terminal exon 1 fragment of mutant huntingtin protein (mHttex1) with expanded polyglutamine (polyQ) repeats in neurons. The first 17 amino acids of the N-terminus of Httex1 (N17 domain) immediately preceding the polyQ repeat domain are evolutionarily conserved across vertebrates and play multifaceted roles in the pathogenesis of HD. Due to its amphipathic helical properties, the N17 domain, both alone and when membrane-associated, promotes mHttEx1 aggregation. Diverse post-translational modifications (PTMs) in the N17 domain alter the aggregation state, thus modulating the cellular toxicity of mHttex1. Furthermore, the N17 domain serves as a nuclear export signal (NES) and mediates the cytoplasmic localization of mHttex1. This review summarizes the four main roles of the N17 domain in regulating HD pathology and discusses potential therapeutic approaches targeting this N17 domain to mitigate HD progression.